A Depiction of the Impact of AI on Human Life in the Film Kamen Rider Zero One Reiwa the First Generation - Miharta, Mohamad Fauzian; Arianingsih, Anisa (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2026)
This research highlights pertinent issues related to the rapid growth and development of the technology of artificial intelligence in the Kamen Rider Zero-One: Reiwa The First Generation film In Tokusatsu Movie. Despite there being many researches on the various Kamen Rider movies that mostly focused on the action scenes, effects, and characterization, few attempts were made to analyze the movie from the point of view of its sociological importance in terms of technology development. The current study will discuss the presentation of the positive and negative aspects of artificial intelligence technology development in relation to Humagears portrayed in this movie. This movie illustrates how the existence of Humagears as an artificial intelligence helps people from all professions in increasing productivity and efficiency. On the other hand, they pose some problems associated with dependency, replacement, and the supremacy of technology over humans. Thus, while the utilization of artificial intelligence technology in the development process poses a threat in terms of the danger associated with it, it also brings progress. A qualitative descriptive approach is employed in the current study, along with a mimetic method of analysis of the film. Dialogue, characters’ interactions, and plot form the core sources for textual analysis in this film.